Cantú Syndrome Resulting from Activating Mutation in the KCNJ8 Gene. Issue 7 (6th May 2014) - Cooper, Paige E.; Reutter, Heiko; Woelfle, Joachim; Engels, Hartmut; Grange, Dorothy K.; van Haaften, Gijs; van Bon, Bregje W.; Hoischen, Alexander; Nichols, Colin G.
<x xml:space="preserve">Abstract</x> Cantu Syndrome (CS) is a rare multi‐organ disorder, characterized by hypertrichosis, cranio‐facial and musculo‐skeletal abnormalities, lymphedema and a host of cardiovascular complications. We now show that, in addition to gain‐of‐function (GOF) in the ATP‐sensitive potassium (KATP) channel regulatory sulfonylurea receptor subunit gene (ABCC9), CS can also result from GOF in the KATP pore‐forming subunit gene (KCNJ8). This demonstrates a novel causal gene and confirms that CS features result from GOF in KATP channel activity, not from non‐channel functions of ABCC9. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>